Put the money where the gaps are: priority areas for climate resilience research in the caribbean - Birthwright A-T, Smith R-A (My University, 2023)
Climate change threatens the fabric of social, environmental and economic existence of Caribbean nations. Countries and regions around the world have been battling the impacts of climate change, with rising temperatures, changing rainfall patterns, more frequent and severe hydro-meteorological events such as hurricanes, droughts, floods, and storm surges, rising sea levels and changing rainfall patterns. The Caribbean region is no exception, and has been identified as the most vulnerable to the impacts of climate change. These island states are not uniform in their vulnerability, and their capacities for effective climate change adaptation and resilience building are also vastly heterogeneous. However, though unique and diverse, their vulnerability is often compounded by common challenges such as their small size, limited capacity to mobilize resources, topography, high debt, and dependence on climate-sensitive sectors.
Keywords: climate change; social fabric; environmental existence; economic existence; Caribbean nations; rising temperatures; rainfall patterns; hydro-meteorological events; hurricanes; droughts; floods; storm surges; rising sea levels; vulnerability